2011
DOI: 10.3892/etm.2011.382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin on apoptosis, NF-κB and NOS gene expression in renal ischemia/reperfusion injury

Abstract: Abstract. The aim of this study was to investigate the effects of quercetin on nitric oxide synthase (NOS), nuclear factor-κB (NF-κB) and apoptosis in renal ischemia/reperfusion (I/R) injury in rats. A total of 42 Sprague-Dawley rats were divided into three groups. The control, I/R and I/R+quercetin (I/R+Q) groups were treated with quercetin (50 mg/kg intraperitoneal) 1 h prior to the induction of ischemia. Tissue malondialdehyde (MDA) and glutathione (GSH) levels were determined by high-performance liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 23 publications
5
46
0
Order By: Relevance
“…Data obtained previously has revealed that ischemic damage is involved with iNOS, while most iNOS is associated with inflammatory causes (22). However, the role of NO in BOO remains controversial.…”
Section: Discussionmentioning
confidence: 98%
“…Data obtained previously has revealed that ischemic damage is involved with iNOS, while most iNOS is associated with inflammatory causes (22). However, the role of NO in BOO remains controversial.…”
Section: Discussionmentioning
confidence: 98%
“…In normal kidney tissues, endothelial NOS is predominantly expressed in the renal blood vessels and capillaries; neuronal NOS is predominantly expressed in the juxtaglomerular macula densa; and iNOS is expressed in the renal medullary thick ascending limb, proximal tubule, distal convoluted tubule and interlobular arteries, arcuate arteries and blood vessels, and other areas of the glomerulus (31). Under a pathophysiological state, iNOS exhibits high levels of expression in mesangial cells, epithelial cells, smooth muscle cells and renal tubular epithelial cells, and there are high levels of infiltrated inflammatory cells, including in the glomeruli and renal interstitium (32).…”
Section: Discussionmentioning
confidence: 99%
“…MDA results from lipid peroxidation and is generally employed as a biomarker of oxidative stress [29-31]. GSH is the main safeguard against oxidative damage by promoting the cellular system of protection against oxidative damage [32]. One related study showed that Vitamin C intake increased GSH levels after renal ischemia injury [33].…”
Section: Discussionmentioning
confidence: 99%